Acute liver failure enhances oral plasma exposure of zidovudine in rats by downregulation of hepatic UGT2B7 and intestinal P-gp - WANG Fan; MIAO Ming-xing; SUN Bin-bin; WANG Zhong-jian; TANG Xian-ge; CHEN Yang; ZHAO Kai-jing; LIU Xiao-dong; LIU Li (Acta Pharmacologica Sinica, 2017)
HIV infection is often associated with liver failure, which alters the pharmacokinetics of many drugs. In this study we investigated whether acute liver failure (ALF) altered the pharmacokinetics of the first-line anti-HIV agent zidovudine (AZT), a P-gp/BCRP substrate, in rats. ALF was induced in rats by injecting thioacetamide (TAA, 300 mg·kg-1·d-1, ip) for 2 days. On the second day after the last injection of TAA, the pharmacokinetics of AZT was investigated following both oral (20 mg/kg) and intravenous (10 mg/kg) administration. ALF significantly increased the plasma concentrations of AZT after both oral and intravenous doses of AZT, but without affecting the urinary excretion of AZT. AZT metabolism was studied in rat hepatic microsomes in vitro, which revealed that hepatic UGT2B7 was the main enzyme responsible for the formation of AZT O-glucuronide (GAZT); ALF markedly impaired AZT metabolism in hepatic microsomes, which was associated with the significantly decreased hepatic UGT2B7 expression. Intestinal absorption of AZT was further studied in rats via in situ single-pass intestinal perfusion. Intestinal P-gp function and intestinal integrity were assessed with rhodamine 123 and FD-70, respectively. We found that ALF significantly downregulated intestinal P-gp expression, and had a smaller effect on intestinal BCRP. Further studies showed that ALF significantly increased the intestinal absorption of both rhodamine 123 and AZT without altering intestinal integrity, thus confirming an impairment of intestinal P-gp function. In conclusion, ALF significantly increases the oral plasma exposure of AZT in rats, a result partly attributed to the impaired function and expression of hepatic UGT2B7 and intestinal P-gp.